EMOTSIONAL HOLATLAR (XX- XXI ASRLAR) - Qurbonaliyev I; Normamatova M; Malikov T; Abdusamadova G. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: In this Thesis, we will mainly provide detailed information about the concept of Emotion, its definitions, and its types.